'Power to the (young) people'? Children and young people's empowerment in the relocation process associated with urban re-structuring. Issue 3 (2nd July 2016) - Lawson, Louise; Kearns, Ade
Abstract : This paper is about children and young people's (CYP) empowerment in the process of urban restructuring, based on parental reflections. Its focus is involuntary relocation in the context of transformational urban regeneration in a Scottish city using cross-sectional and longitudinal qualitative data, based on 20 family households (at wave 1) comprising 40 CYP. Specifically, we are interested in how empowerment plays out – directly or indirectly – in the private space of the family and home, and for different age groups. We identified three sets of 'empowerment' or decision-making situations where CYP were involved: rationalising the need to move; deciding where to move to; and helping children cope and adjust to change. We found that empowerment differs by age and varies between pre-move discussions, decision-making and post-move dislocation and other outcomes. In the 'Discussion' section to this paper, we raise issues about relocation from one deprived neighbourhood to another; parental objectives to avoid social disruption for their children; and, the effects of distance upon empowerment. We can see some degree of empowerment for CYP in terms of securing better outcomes after relocation.